Development of Learning Media Based on Mobile Learning Applications - Sinaga, Risma Margaretha; Trisnaningsih, Trisnaningsih; Pujiati, Pujiati; Sudarmansyah, Didi (FKIP Universitas Lampung, 2019)
Development of mobile learning application-based media. Objectives: The purpose of this studyis to develop a more dynamic learning media by utilizing technology in the form of applications on smartphone devices to improve student learning outcomes. Methods: This study uses research anddevelopment methods with data collection techniques in the form of questionnaires, feasibility tests and effectivenessof mobile learning applications developed as learning media through stages designed according to the ADDHIE model. Findings: Product development in the form of mobile learning applications is feasible as a learning medium and effective for improving student learning out comes with an increasein the average value of 28 students from 57.32 to 81.43. Conclusion: Mobile learning application is a good choice as a learning media. Keywords: Learning media, mobile learning application, research and development DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201907